Strategi Pengembangan Bisnis Pada Umkm Daging Segar Kios PD Rai Raka di Pasar Caringin - Maulana, Bima Rizky Rahmat; Akbar, Ridho Riadi; Muttaqin, Ridlwan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to develop business strategies for PD Rai Raka, an SME engaged in selling fresh beef at Pasar Caringin, Bandung. The research addresses challenges such as intense competition with digitalized competitors, raw material price fluctuations, and the lack of modern marketing strategies. The qualitative approach with descriptive-analytical techniques was employed. Data were collected through in-depth interviews, observations, and document analysis, then processed using the SWOT matrix to identify strengths, weaknesses, opportunities, and threats. The analysis revealed that PD Rai Raka has strengths in product quality, strategic location, and loyal customers. However, weaknesses such as limited digitalization and inconsistent product quality hinder business growth. Opportunities, including digitalization trends and strategic partnerships, can be leveraged to expand the market. Threats from digital-savvy competitors and fluctuating raw material prices require adaptive strategies. In conclusion, PD Rai Raka’s business development can be achieved through digital integration, product diversification, efficient stock management, and modern promotion strategies. These measures are expected to enhance competitiveness and business sustainability in a dynamic market environment.